The The Impact Of The Postponement Of Halal Certification Obligations For MSMEs In Indonesia: Challenges And Opportunities - Mazidah, Bayyinatun; Fitriyani, Nurul (Journal of social Philantrophy and Halal Research, 2026)
This study aims to analyze the socio-economic impact of the postponement of halal certification obligations on MSMEs, identify the challenges faced by business actors, and explore opportunities that arise during the delay period. The method used is a qualitative literature study by examining various sources from scientific journals, government regulations, and related institutional reports. The results of the study show that the postponement of halal certification provides room for improvement for the government and MSMEs in terms of socialization, cost, and certification infrastructure. However, if not used properly, this delay can slow down the achievement of Indonesia's target as the center of the world's halal industry. Synergy is needed between the government, certification bodies, and MSME actors to strengthen the competitiveness of the national halal economy.